ANALYSIS OF ANTENNA SPECIFICATION FOR VERY HIGH RESOLUTION SATELLITE DATA ACQUISITION THROUGH DIRECT RECEIVING SYSTEM (DRS) - Muchammad Soleh; Ali Syahputra Nasution; Arif Hidayat; Hidayat Gunawan; Ayom Widipaminto (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2018)
Very High Resolution Satellite Image (VHRSI) data for Indonesian Government license is required by ministries/agencies, TNI, police, and local government to support national programs. But Indonesia did not have a VHRSI data recipient facility to directly acquire this data. In accordance with Law 21/2013 on Space, LAPAN is mandate to provide high resolution satellite data, and based on a roadmap for provision of satellite data in 2017, LAPAN will provide a VHRSI data reception facility through direct receiving system (DRS). This will be more efficient than other methods in providing the data. Priority provision of satellite data is for acquiring Pleiades and TerraSAR-X operating in the frequency range 8 GHz (X-Band). Therefore, to receive both data, it requires antenna subsystem with optimum coverage throughout Indonesia. Parameters to obtain the minimum antenna specifications include Free Space Loss (FSL), Carrier to Noise Ratio (C/No) and Antenna Gain to Noise Temperature (G/T). The calculation of G/T antenna is done for both satellites based on satellite parameters and analysis of antenna product availability in the market. Based on the calculation of satellite parameters shows that the minimum G/T value with the elevation of 5 degrees is 27.71 dB/K for Pleiades data reception and the minimum G/T value of 26.10 dB/K for the TerraSAR-X data reception. In general, the minimum G/T value for receiving the Pleiades and TerraSAR-X data is at 28 dB/K. While based on the calculation of antenna products availability in the market is require G/T value of 33.45 dB /K for the elevation of 5 degrees with a diameter of 7.5 mm antenna. This can be conclude that the antenna products meets the minimum requirements specification and to receive both satellite data. However, both calculation for the antenna subsystem still will be evaluated further in order to be directly installed at Parepare Remote Earth Station (SPBJ), South Sulawesi.